LANs to WANs : the complete management guide - Muller, Nathan J. (Artech House telecommunications library., 2003)
Empowered by today's high-performance computers interconnected over LANs and WANs, companies are faced with the daunting task of bringing workability to the diversity and complexity of today's data communications landscape. This new, comprehensive resource addresses key network management challenges, showing you how to: tie together incompatible LANs, meld legacy systems and LANs, extend the reach of LANs with wireless links, protect information assets from various disaster scenarios, and consolidate multi-protocol traffic over a single WAN backbone in a way that guarantees appropriate service levels.